Influence AGI Shopping Motives toward Impulse Buying with Internet Browsing as a Mediator - Siska Putri Noviantari; Conny Tjandra Rahardja (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study uses AGI shopping motivation as the independent variable, impulse buying as the dependent variable and internet browsing as the mediating variable. The data used is primary data obtained through distributing questionnaires using Google Form with data obtained as many as 320 respondents. Purposive sampling is a sampling technique used in this study, by taking consumers who have done online shopping at least six times in one year. The method used in data processing is a structural equation model (SEM). The purpose of this study was to determine how the influence of AGI motives on impulse buying mediated by internet browsing activities. The results of this study conclude that (1) the AGI motive has a positive and significant effect on impulse buying, (2) the AGI motive has a positive influence on internet browsing, (3) internet browsing has a positive influence on impulse buying, and (4) internet browsing is a partial mediator of the relationship between AGI motives and impulse buying.